Filling Information Gap on Covid-19 Pandemic Using Proverbs and Figurative Language: Lilaphalapha Facebook Page Lesotho - Mokala, Ntsoaki Teresa; Matee, Lihotetso Gloria; Khetoa, Soyiso Godsave (Journal of Languages and Language Teaching, 2023)
The current study reports on ways in which Lilaphalapha page on Facebook used language to provide awareness on Corona virus pandemic. Corona Virus affected the whole universe in different ways. Like the rest of the world, to curb the spread of the virus, Lesotho declared a state of emergency and the government put different health protocols in place. To prevent the widespread of COVID-19, a wealth of knowledge was provided in Indo-European languages in many countries. Speakers of African languages such as Sesotho, a national language of Lesotho, had to be innovative and employ region specific methodologies to spread awareness about COVID-19 pandemic.Â  In this qualitative research, data was collected from eight purposely selected episodes posted on Lilaphalapha page on Facebook in April 2020. The videos were analysed through inductive thematic analysis approach. The paper analysed how the use of proverbs and figurative language has helped in preserving Sesotho as a language and filled the gap in preventing language dearth particularly in the advent of COVID-19 pandemic. The findings indicated figurative language, humour and proverbs were used in spreading COVID-19 awareness to Basotho.Â